Knowledge of outdoor workers on the effects of natural UV radiation and methods of protection against exposure. (April 2016) - Hault, K.; Rönsch, H.; Beissert, S.; Knuschke, P.; Bauer, A.
Abstract: The most important but influenceable risk factor in the development of skin cancer is the unprotected exposure to solar ultraviolet (UV) radiation. In order to assure adequate and effective protection against UV exposure, a level of knowledge about solar radiation and its effects is required. The objective of this study was to assess the knowledge of workers in outdoor professions on the effects of natural UV radiation and methods of protection against exposure. Forty outdoor workers were given a standardized questionnaire designed to ascertain their level of knowledge. The majority of participants knew exposure to solar radiation can be detrimental depending on exposure time. Eighty‐three percentage recognized that people working regularly in an outdoor environment may be at risk due to high exposure. Long‐sleeved clothing plus headgear and sunscreen containing sun‐protecting substances were deemed adequate methods of protection by 83% and 85% respectively. Seventy percentage of the outdoor workers were familiar with the definition of the sun protection factor (SPF), yet only 25% correctly identified the amount of sunscreen needed to achieve the SPF as indicated on the product. A mere 8% of participants knew that symptoms of a sunburn first became apparent 3 h after sun exposure and only 18% were able to accurately gauge the amount of time they could spend in the sun before developing one. Although 30% had heard of the ultraviolet index (UVI), only 13% understood that protecting your skin using additional measures is recommended as of UVI 3. Overall, 30% of the outdoor workers thought themselves sufficiently protected against the harmful effects of the sun. While the participants of this study had a basic fundamental understanding of the effects of solar radiation and methods of protection against exposure, there remains an urgent need for further clarification across all demographic groups.